Enhancement of the anisotropic thermoelectric power factor of topological crystalline insulator SnTe and related alloys via external perturbations - Yarmohammadi, Mohsen; Mirabbaszadeh, Kavoos (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
Topological crystalline insulators (TCIs) possess linearly dispersed metallic surface states, which are protected by crystal point group symmetries. The ability to fine-tune the effective mass of surface Dirac fermions by breaking their crystalline symmetry is highly desirable for thermoelectric applications. Given that the signatures of SnTe and its family originate from the (001) surface states, a natural question is: how does the thermoelectric performance of these states change due to the emergence of massive Dirac fermions? Herein, various physical perturbations, subjects of lively discussions, have been uncovered to improve the thermoelectric power factor (PF) of SnTe (001) and related alloys. Furthermore, orientation-dependent charge and heat currents are explored in detail. The surface-state Onsager transport calculations are performed using the Kubo–Greenwood approach. Highly dispersive and degenerate energy bands originating from the band gap opening are responsible for the enhancement of PF. While the x -direction has contributed mostly to the PF of the system, we report exceptional 74.65%, 121.67% and 110% enhancement of the PF compared with the pristine case at a temperature of 540 K when we perturb the crystalline mirror symmetry by strain, exchange field (stemming from proximity coupling to a ferromagnet, or the electric field, or Zeeman magnetic field) and Rashba spin–orbit coupling, respectively. The predicted PFs propose a new research direction to experimentalists to save time and to focus only on the thermal conductivity of SnTe (001) to achieve the highest thermoelectric efficiency.